2006
DOI: 10.1590/s0034-72992006000500014
|View full text |Cite
|
Sign up to set email alerts
|

Audiometria de alta freqüência em adultos jovens e mais velhos quando a audiometria convencional é normal

Abstract: Hi gh-frequency audiometry can detect early changes in auditory sensitivity resulting from processes such as aging. Nonetheless its use is still limited, and additional studies are required to establish its use, particularly among older adults. Aim: To compare pure tone thresholds for frequencies from 250 Hz to 16 kHz in young and older adults, with or without audiologic complaints. Method: Pure tone sensitivity to 250 Hz to 16 kHz was assessed with an AC-40 audiometer in 64 adults, evenly distributed in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
6
0
9
Order By: Relevance
“…On the other hand, other authors described the lack of significant interaural difference in the auditory thresholds between the RE and LE obtained in their studies 8,14 . We have also found authors who reported that the mean values obtained for the RE and LE together, without analyzing a possible significant interaural difference 15,19,27 . This difference in the auditory thresholds between the RE and LE in the NSG was an intriguing fact for which we have not found any explanation so far in the literature studied.…”
Section: Discussonmentioning
confidence: 65%
See 1 more Smart Citation
“…On the other hand, other authors described the lack of significant interaural difference in the auditory thresholds between the RE and LE obtained in their studies 8,14 . We have also found authors who reported that the mean values obtained for the RE and LE together, without analyzing a possible significant interaural difference 15,19,27 . This difference in the auditory thresholds between the RE and LE in the NSG was an intriguing fact for which we have not found any explanation so far in the literature studied.…”
Section: Discussonmentioning
confidence: 65%
“…Numerous authors also found associations between smoking and hearing loss in LF 6,9,10,22,[25][26][27][28][29] . Hearing loss in HF can be 1 to 1.33 times higher among smokers 24 .…”
Section: Discussonmentioning
confidence: 99%
“…Thus, the high-frequency hearing thresholds were higher in older individuals, probably as a result of loss of auditory sensitivity due to the aging process. Silva and Feitosa (21) performed high-frequency audiometry in 64 individuals divided into two groups: one composed of the 25-35-year age group and another of the 45-55-year age group, and verified that the greater the age, the higher the responses to the hearing thresholds, with more significant difference at the higher frequencies (8 to 16 kHz). The same was reported by Figuerêdo and Corona (4) in their study conducted with 30 individuals aged 19-56 years analyzing pure-tone thresholds by conventional audiometry: the control group composed of older individuals showed influence of age on their hearing thresholds, evidencing a decrease in auditory sensitivity with increasing thresholds in all statistically significant frequencies.…”
Section: Discussionmentioning
confidence: 93%
“…Diversos fatores na execução do exame de AAF devem ser considerados, pois podem levar a variações dos resultados, tais como: treinamento prévio do sujeito na realização do exame, tipo de audiômetro utilizado para a avaliação auditiva de tons de alta frequência, calibração do equipamento segundo referência do decibel em nível de audição (dBNA) ou em nível de pressão sonora (dBNPS) e o posicionamento do fone no ouvido, que pode interferir na precisão do exame devido às características de ressonância do meato acústico externo para sinais acima de 15 kHz, podendo ocorrer variações de 15 a 20 dB na resposta do sujeito; também poderá ocorrer maior possibilidade de efeito do colabamento do meato acústico externo, principalmente na avaliação das altas frequências (13,27) .…”
Section: Padrões Técnicos Utilizados Nas Aafunclassified